Dynamics Modeling and Vibration Characteristic Analysis of Star Gear Train with Herringbone Gears - Lulu Qian; Peng Lou; Jin Feng; Jian Luo; Zhongtao Huang (Jixie chuandong)
Taking a herringbone gear transmission system with star gear train as the research object and based on the finite node method，a system-level dynamics model considering shaft-bearing-rigid rotor and the meshing of gears is established. The dynamic characteristics of the system are analyzed based on the RMS of vibration velocity at the bearings with the rotation speeds. Then the theoretical analysis results are compared with the experimental data to verify the reliability of the proposed model. After that，based on the analysis of vibration characteristics and modal characteristics of the gear system，resonance localization and resonance cause analysis are carried out. The results show that the theoretical analysis is in good agreement with experimental results. This study provides a valuable reference method for resonance prediction and resonance cause analysis of herringbone gear transmission system of star gear train.